Three Rice NAC Transcription Factors Heteromerize and Are Associated with Seed Size - Mathew, Iny Elizebeth; Das, Sweta; Mahto, Arunima; Agarwal, Pinky (Frontiers in Plant Science, 2016)
NACs are plant-specific transcription factors (TFs) involved in multiple aspects of development and stress. In rice, three NAC TF encoding genes, namely ONAC020, ONAC026, and ONAC023 express specifically during seed development, at extremely high levels. They exhibit significantly strong association with seed size/weight with the sequence variations located in the upstream regulatory region. Concomitantly, their expression pattern/levels during seed development vary amongst different accessions with variation in seed size. The alterations in the promoter sequences of the three genes, amongst the five rice accessions, correlate with the expression levels to a certain extent only. In terms of transcriptional properties, the three NAC TFs can activate and/or suppress downstream genes, though to different extents. Only ONAC026 is localized to the nucleus while ONAC020 and ONAC023 are targeted to the ER and cytoplasm, respectively. Interestingly, these two proteins interact with ONAC026 and the dimers localize in the nucleus. Trans-splicing between ONAC020 and ONAC026 results in three additional forms of ONAC020. The transcriptional properties including activation, repression, subcellular localization and heterodimerization of trans-spliced forms of ONAC020 and ONAC026 are different, indicating toward their role as competitors. The analysis presented in this paper helps to conclude that the three NAC genes, which are associated with seed size, have independent as well as overlapping roles during the process and can be exploited as potential targets for crop improvement.